The Effect of Work Stress, Organizational Commitment, and Job Satisfaction on Turnover Intention - Oktavia Syafaatun; Tine Yuliantini (Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study aims to examine the effect of work stress, organizational commitment & job satisfaction on Turnover Intention at PT. Jakarta Aquarium. The population in this study were 117 employees, with a sample of 90, and 27 employees as trials in the instrumental test. The design of this study is quantitative causality, assisted by the PLS statistical method, and uses a Likerd measurement scale. Methods of data collection using survey methods, with the research instrument is a questionnaire. The techniques used in data collection are Library Research, Field Research, and saturated sampling. The results of this study prove that work stress has a significant positive effect on Turnover Intention, and organizational commitment and job satisfaction have a significant negative effect on Turnover Intention.